Biosurfactant: A Next-Generation Tool for Sustainable Remediation of Organic Pollutants - Sharma, Neha; Lavania, Meeta; Lal, Banwari (Frontiers in Microbiology, 2022)
The energy resources are petroleum hydrocarbons that contribute pollutants majorly into the environment. These pollutants may cause serious health issues and hence, the consideration has been remunerated in the development of alternative technologies for the mitigation of these contaminants sustainably without causing any pollution. One such alternative is biosurfactants produced by numerous microbial species have tendency to remediate organic pollutants. Biosurfactants are amphiphilic compounds that are categorized into two types based on their molecular mass. Biosurfactant can be generated extracellular or intracellular as a part of the cell membrane of bacteria. The review involves the insight view of type of surfactants, their properties and mechanism in degradation of oil spills.